Construction of reinforced concrete floor slab / Nur Anis A. Rahman - A. Rahman, Nur Anis (Universiti Teknologi Mara, Perak, 2014)
In a nutshell, this practical training report is about the process and method that involved for the construction of the suspended concrete reinforced floor slab. I have made this practical training report based on my experience for 4 months on the site. This practical training report have some parts, it is divided with the company background and my case study background. Based on the my experience and observation at the site ,the construction of the reinforced concrete floor slab very complicated to be construct. There have many methods that must to be doing and to be process to construct a reinforced concrete floor slab. In this report there be contained the summary of the construction of the reinforced concrete floor slab, that in this report there include the material, equipment, components and machinery that used for the construction of the reinforced concrete floor slab. Besides, in this practical training report also, I have included with the method of the how to construct the reinforced concrete floor slab. Hence, It is started from the formwork for the floor slab, from make it the floor slab board that made from the timber and wood, installation of beam steel structure, installation of the service pipe and wiring conduit such as sewerage pipe, electrical conduit and telecommunication conduit, installation of Brc on the floor formwork and then placement work for the concrete. When the construction process of the reinforced concrete floor slab being held, there have several problems that arise that have been identified for the construction of the floor slab,this practical training report has been include with the several comment and recommendation from my opinion that can solve the problems that arise. In conclusion, from this practical training report that I has done can explain with detailed to all the reader about the construction of the reinforced concrete floor slab.